A review of the re-structuring of the Nelson Mandela Academic Hospital through the change management approach - Nodikida, Mzulungile (Rhodes University, Faculty of Commerce, Rhodes Business School, 2018)
The research used a change management approach to analyze the restructuring of the Nelson Mandela Academic Hospital from a tertiary to a central hospital. The study was underpinned by two objectives. Firstly, to analyze the restructuring of the Nelson Mandela Academic Hospital from a tertiary to a "central" hospital using the Core Elements Framework of change management developed by Antwi and Kale (2014). Secondly, to use the knowledge gained through literature review combined with the experiences of the managers at Nelson Mandela Academic Hospital to inform future healthcare reforms in general and particularly in the restructuring of hospitals. The Core Elements Framework by Antwi and Kale (2014) identifies six fundamental change elements from both emergent and planned change management approaches. The six elements are regarded by theorists from the two different schools of thought i.e. emergent change and planned change as key for successful change. The Core Elements Framework by Antwi and Kale, (2014) demonstrates the strength of not viewing the two approaches to change management as mutually exclusive but as complementing each other when the other is falling short. The study identified the following: ■ The change was prompted by clearly identifiable external factors more than internal factors. ■ There was notable lack of organizational harmony which may have negatively impacted the change process. ■ The Private Public Partnership (PPP) funding model which was aimed at delivering the central hospital collapsed, after a study discovered that it benefited the private sector more than the public sector. ■ There was no proper consultation of major stakeholders for preparation of the change. ■ Resources in all material forms were not made available for the change to take off, this means that there was no organizational capacity to execute the change. The study draws the conclusion that lack of organizational capacity, organizational harmony and a proper consultation process for stakeholders are the main reasons why the restructuring of the Nelson Mandela Academic Hospital is not yielding the desired results. The study recommends that organizations should implement a multidimensional approach for any change initiative to be successful and that organizations must ensure the availability of the necessary resources when embarking on change.
Keywords: Organizational change -- Case studies; Organizational change -- Management; Reengineering (Management) -- South Africa -- Mthatha; Leadership -- South Africa -- Mthatha; Organizational behavior -- South Africa -- Mthatha; Corporate culture -- South Africa -- Mthatha; Nelson Mandela Academic Hospital